A Prediction and Simulation Model for Target-Oriented Regional Citrate-Calcium Anticoagulation in Extracorporeal Blood Purification. Issue 10 (October 2016) - Brandl, Martin; Kellner, Karlheinz
Aims: Regional citrate-calcium anticoagulation is becoming more and more attractive for extracorporeal treatments in the clinical routine. Methods: A prediction and simulation tool for the safe application of RCA during extracorporeal treatments was introduced. The model predicts the course of the ionized calcium level in the patient and the current anticoagulation status in the extracorporeal circuit based on the actual settings of the dialysis machine. Results: The simulation tool delivers areas in which the blood and dialysate flow can be adjusted to reach the desired target values for RCA and predicts the time course of several parameters during treatment.